LOOKING FOR POSSIBLE DARK MATTER FREE PROGENITORS OF THE CARINA DWARF SPHEROIDAL GALAXY USING N-BODY SIMULATIONS - Diego F Castellanos; Rigoberto A. Casas-Miranda (Momento, 2018)
We present a study of the evolution of several different dark matter free possible progenitors of the Carina dSph galaxy, one of the satellites of the Milky Way, using Newtonian numerical N-body simulations. It was not possible to reproduce all the observed properties of Carina, therefore a possible dark matter free progenitor of it was not found; nevertheless, progenitors with initial mass 1x107 M. and Plummer radii 0.5 and 0.6 kpc reproduced the observational values of Carina for three of the five studied variables (half light radius, line-of-sight velocity dispersion and galactocentric distance). Thus, those satellites could be the starting point for further work about the origin of the Carina dwarf galaxy.